Outcomes of Pectoralis Major Tears in Active Duty US Military Personnel: A Comparison of Surgical Repairs Performed in the Forward Deployed Setting to Those Performed in the Continental United States. Issue 11 (20th April 2019) - Shakir, Irshad; Davis, William; Choate, W Stephen; Antosh, Ivan J; Parada, Stephen; Salazar, Dane H
Abstract: Introduction: The purpose of our study is to compare pectoralis major tears in active duty military personal repaired surgically in the forward deployed setting to those performed in the Continental United States. Materials and Methods: Retrospective comparison of all pectoralis major tendon repairs performed at Madigan Army Medical Center from 2000 to 2007 to a forward deployed series treated by two deployed United States Air Force orthopedic surgeons at one expeditionary medical treatment facility over a 4-month deployment cycle from December 2013 through March 2014. Results: Fourteen patients from the CONUS group and eight patients from deployed group were compared; they had a mean age of 32 years (21–52) all with pectoralis major ruptures that underwent operative fixation. Nineteen of the 22 patients (86%) sustained their injuries during bench press. The average bench press weight was similar with 271.8 lbs in the CONUS group and 273.1 lbs in the deployed group. There were 9 complete tears and 5 partial tears in the CONUS cohort whereas 7 complete tears and 1 partial tear in the deployed cohort, with all tears in both groups occurring at the insertion of the humerus. All 22 patients in both cohorts denied the use of anabolic steroids. The average DASH score at final follow-up was 12.74 in the CONUS group and 36.44 in the deployed group. The CONUS group reported that 7 out of 8 immediate repair patients and 4 out of 6 delayed repair patients returned to functional work level within 6 months with the 2 patients in the delayed repair group taking longer than 9 months to return to work. The deployed members reported return to functional work level at an average of 6.5 months. Both cohorts had early return to weight lifting at 6 and 7 months, respectively. The CONUS group reported a 39% bench press weight reduction and 34% pushup maximum reduction whereas the deployed cohort reported a 20% and 8% reduction respectively. Conclusions: When comparing deployed to CONUS results, we demonstrated that surgical repairs at one permanent US military in-theater tertiary referral medical center were as successful as repairs performed at one CONUS US Army academic tertiary referral medical center. Although in-theater surgical repair was technically feasible and clinically successful, we believe the lengthy convalescence, stringent post-operative restrictions, demanding environment and impact on operational readiness should preclude deployed surgical repairs from becoming standard practice.